The Efficacy of Noninvasive 1060-Nm Diode Lasers for Submental Lipolysis: A Pilot Study - Wanitphakdeedecha R; Evangelista KER; Yan C; Apinuntham C; Techapichetvanich T; Eimpunth S; Lektrakul N; Manuskiatti W (Dove Medical Press, 2022)
Rungsima Wanitphakdeedecha,1 Kristy Elleza R Evangelista,1,2 Chadakan Yan,1 Chalermkwan Apinuntham,1 Thanya Techapichetvanich,1 Sasima Eimpunth,1 Nittaya Lektrakul,3 Woraphong Manuskiatti1 1Department of Dermatology, Faculty of Medicine Siriraj Hospital, Mahidol University, Bangkok, Thailand; 2Department of Dermatology, Research Institute for Tropical Medicine, Manila, Philippines; 3Department of Radiology, Faculty of Medicine Siriraj Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Rungsima Wanitphakdeedecha, Department of Dermatology, Faculty of Medicine Siriraj Hospital, Mahidol University, 2 Prannok Road, Bangkok Noi, 10700, Thailand, Tel +66 2 419 4333, Fax +66 2 411 9922, Email rungsima.wan@mahidol.ac.thBackground: Submental fat is a noticeable fat in the submental region that is of great concern aesthetically, especially to female patients. A 1060-nm diode laser is a clinically proven device for the laser lipolysis of subcutaneous fat cells. This study aimed to evaluate the safety and efficacy of a 1060-nm diode laser for submental fat reduction.Methods: Twenty subjects with unwanted localized submental fat were treated with a single session of a 1060-nm diode laser with an energy setting between 0.95 and 1.40 W/cm2, depending on each patient's tolerance. Submental fat thickness measurements were documented at baseline, and 1, 3, and 6 months after treatment. Clinical photographs, ultrasound images, and adverse events were evaluated at each follow-up visit. Subjects responded to a satisfaction questionnaire at the end of the study.Results: The subjects had a mean age of 34.55 ±  6.19 years, a mean body weight of 70.66 ±  10.55 kilograms, and most (95%) were women. The average energy setting was 0.95- 1.40 W/cm2, with a pain score of 3.90 ±  1.30 on a 0-to-10 scale. A significant reduction in submental fat thickness measured by ultrasound was noted at post-treatment month 3 (falling to 0.46 ±  0.13; P =  0.013). However, there was a slight increase in the submental fat thickness at the 6-month follow-up (to 0.48 ±  0.12); the change in the thickness relative to the baseline was nonsignificant (P =  0.121). Most subjects reported an improvement 6 months after the treatment. No severe adverse events were observed throughout the study period.Conclusion: Our study demonstrated the potential role of 1060-nm Diode laser for the treatment of localized submental subcutaneous adiposities. It is a promising alternative treatment modality for patients seeking an in-office, nonsurgical procedure for fat reduction without severe complications.Keywords: 1060-nm, diode laser, lipolysis, submental fat